2021
DOI: 10.1080/13621718.2021.1884801
|View full text |Cite
|
Sign up to set email alerts
|

Refill Friction Stir Spot Welding (Refill FSSW) of magnesium lithium alloys: effects of air and argon cooling

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The joining of 1.53-mm ZEK-100 Mg alloy sheet and 1-mm Zn-coated DP600 steel sheet was achieved by Chen et al [35] with the RFSSW process, and the research found that the Zn coated promoted the formation of FeAl 2 at the interface of the joint in the process, thus enhancing the strength of the joint. In order to reduce the oxide inclusions generated in the LZ91 Mg-Li alloys during the RFSSW process, Zhang et al [36] proposed RFSSW with argon cooling, and a joint with flat and smooth surfaces was achieved.…”
Section: Friction Stir Spot Weldingmentioning
confidence: 99%
“…The joining of 1.53-mm ZEK-100 Mg alloy sheet and 1-mm Zn-coated DP600 steel sheet was achieved by Chen et al [35] with the RFSSW process, and the research found that the Zn coated promoted the formation of FeAl 2 at the interface of the joint in the process, thus enhancing the strength of the joint. In order to reduce the oxide inclusions generated in the LZ91 Mg-Li alloys during the RFSSW process, Zhang et al [36] proposed RFSSW with argon cooling, and a joint with flat and smooth surfaces was achieved.…”
Section: Friction Stir Spot Weldingmentioning
confidence: 99%
“…Air cooling systems have been widely applied to Li‐ion battery packs due to simplicity and electrical safety. Zhang et al 4 proposed an air cooling method for herringbone fin long sleeve battery pack, and proved the effectiveness of the method by comparing with the fin less and sleeve less schemes. Li et al 5 improved the cooling effect of the battery by optimizing the air flow structure and layout of the U‐type air‐cooled battery thermal management system.…”
Section: Introductionmentioning
confidence: 99%
“…The RFSSW process squeezes the extrusive material into the weld by a complex movement with a probe, a sleeve and a clamping ring [17]. There is no keyhole appeared in the weld after the welding process [18]. However, the RFSSW process is not widely used in industry due to the complexity of the manufacturing equipment [19,20].…”
Section: Introductionmentioning
confidence: 99%